PERAN PENYULUH PERTANIAN DALAM USAHATANI PADI SAWAH DI DESA KOSIO BARAT KECAMATAN DUMOGA TENGAH KABUPATEN BOLAANG MONGONDOW - Andre Reynhart Mangare; Jean Fanny Junita Timban; Noortje Marsellanie Benu (Sam Ratulangi University, 2021)
This research aims to determine the role of extension workers in improving rice farming in West Kosio Village, Dumoga Tengah District. This research was conducted from October to December 2020 at Kosio Barat Village, Dumoga Tengah District, Bolaang Mongondow Regency. The method used is a survey method by taking primary data obtained through direct interviews using a list of questions (questionnaires), and secondary data obtained from the village office, as well as related agencies. Sampling used simple random sampling method, with a sample of 25 rice farmers in West Kosio Village and 1 extension worker in West Kosio Village, a total of 26 respondents. The results showed that the percentage index of the role of extension workers in rice farming was 54% (less role).